Case Report: Potocki-Lupski Syndrome in Five Siblings - Grama, Alina; Sîrbe, Claudia; Miclea, Diana; Cǎinap, Simona Sorana; Huniadi, Delia; Bulata, Bogdan; Pop, Tudor Lucian (Frontiers in Pediatrics, 2021)
Potocki-Lupski syndrome (PTLS) is a rare developmental disorder resulting from the partial duplication of the short arm of chromosome 17. Affected children may have hypotonia, facial dysmorphism, or neurological abnormalities. PTLS is also frequently associated with failure to thrive due to swallowing difficulties or growth hormone deficiency. We report the first Romanian family (a mother and her five children) diagnosed with PTLS (17p11.2 microduplication). Fortunately, they present a less severe form of the disease. The neurological manifestations (speech delay, mild intellectual disability) are associated with craniofacial dysmorphism (microcephaly, micrognathia, triangular face, broad forehead, long chin, prominent ears, dolichocephaly, down slanting palpebral fissures). The diagnostic was established using a multiplex ligation-dependent probe amplification technique (MLPA) test, which detected the duplication of three regions of the 17p11.2 chromosome (RAI1, DRC3-6, LLGL1-4RA). Children with PTLS have specific phenotypes (craniofacial dysmorphism or neurological manifestations), which must draw the pediatrician’s attention to a possible genetic condition. However, every child with this disease is unique and may have a different clinical presentation. A multi-disciplinary team is needed for the management of these patients. The parent’s counseling and genetic advice are essential for a family with children with PTLS.